Verti-zontal differentiation in export markets - Francesco Di Comite; Jacques-François Thisse; Hylke Vandenbussche (European Central Bank (ECB), 2014)
Many trade models of monopolistic competition identify cost efficiency as the main determinant of firm performance in export markets. To date, the analysis of demand factors has received much less attention. We propose a new model where consumer preferences are asymmetric across varieties and heterogeneous across countries. The model generates new predictions and allows for an identification of horizontal differentiation (taste) clearly distinguished from vertical differentiation (quality). Data patterns observed in Belgian firm-product level exports by destination are congruent with the predictions and seem to warrant a richer modelling of consumer demand.
Keywords: D43; F12; F14; L16; 330; asymmetric preferences; heterogeneous consumers; heterogeneous firms; monopolistic competition; product differentiation